THE EFFECT OF REWARD MANAGEMENT ON EMPLOYEE PERFORMANCE IN SELECTED PRIVATE SECTOR ORGANIZATION IN ANAMBRA STATE, NIGERIA - OGBU, KENNETH CHUKWUEMEKA,PHD,; EWELIKE, UCHENNA EUGENE,PHD,; UDEH, ONYINYE JUSTINA, (IJRDO - Journal of Applied Management Science, 2020)
The study examined the effect of rewards management on employee performance in the organization, using selected private sector organizations in Anambra State as the study area. The literature was partitioned into four main sections namely; conceptual review, theoretical framework, theoretical exposition and empirical review. The study adopted descriptive survey design. Statistical tools of analysis include summary statistics of percentages, Pearson correlation and multiple regression analysis. Preliminary results of the study showed that the model is statistically significant given F-value of 16.399 and the significance level of 0.000 which is less than P ≤ 0.05. The regression coefficient of 0.681 shows that 68.1 percent of relationship exists between the dependent and independent variables. Similarly, the coefficient of determination ‘R2’ which has a value of 0.639 shows that 63.9 percent variation in the dependent variable can be explained by the independent variables. Major findings from the study indicate that extrinsic and intrinsic rewards have positive and significant effect on employee performance in the organization. The study concludes that extrinsic and intrinsic rewards motivate employees to put up enhanced performance in their organizations. However, whereas extrinsic rewards appeals more to lower level wage employees, the higher level wage employees appreciate the intrinsic rewards more than the financial rewards. The study recommended among others that the manager should be properly guided while administering rewards so as to achieve efficient and effective results in the process.